Digital Marketing and Brand Image as Drivers of Customer Loyalty at PT Bank OCBC NISP Tbk Pettarani Makassar Branch - Devi Alvionita; Amir Jaya; Jerliyen Pramita Londong (Management Study Program, Universitas Kristen Indonesia Paulus, 2025)
The development of digital technology has brought significant changes in various sectors, including the banking industry. These changes encourage financial institutions, including PT Bank OCBC NISP Tbk KC Pettarani Makassar, to further develop more relevant and effective marketing strategies, one example of which is through the implementation of digital marketing. Digital marketing plays an important role in shaping brand image. However, in practice, not all financial institutions are able to implement this strategy optimally. At OCBC Bank, the digital marketing strategy is considered not yet capable of attracting attention and building customer loyalty to the maximum. This condition directly impacts the brand image formed in the minds of customers, which ultimately affects their loyalty. This research aims to identify various factors influencing the decline of customer loyalty and to formulate appropriate digital marketing strategies to enhance that loyalty. The research method used in this study is Structural Equation Modeling - Partial Least Squares or SEM-PLS. The results of this study provide insights that digital marketing does not have a direct impact on customer loyalty. Customer loyalty is more influenced by the brand image of Bank OCBC. This is evidenced by the path coefficient value of brand image towards loyalty being higher than the path coefficient value of digital marketing towards customer loyalty.